EKSPLORASI PROGRAM POJOK BACA UNTUK MENUMBUHKAN MINAT BACA SASTRA ANAK PADA SISWA KELAS IV SDN RAWABADAK SELATAN 03 - DEWINTA PRAMONOPUTRI, TRIAMBAR; AMELIA, DECENNI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low reading interest of elementary school students remains a major challenge in strengthening literacy culture in Indonesia. One of the strategies implemented by schools to foster students' reading interest is the reading corner program. However, its implementation has not been fully optimized, particularly in promoting children's literature reading interest. This study aimed to describe the condition of the reading corner, identify the availability of children's literature books, and examine the responses of teachers and students regarding the contribution of the reading corner program to fostering children's literature reading interest at SDN Rawabadak Selatan 03. This study employed a qualitative approach using a descriptive method. The research participants consisted of the principal, the fourth-grade teacher, and fourth-grade students. Data were collected through observation, interviews, and documentation and were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings revealed that the reading corner had been provided and utilized as a supporting facility for literacy activities, although its management still required further improvement. The availability of children's literature books was relatively adequate; however, both the quantity and variety of the collection need to be expanded to better accommodate students' interests and needs. Teachers and students responded positively to the reading corner program because it increased students' interest in reading, encouraged literacy habits, and motivated them to read children's literature independently. Therefore, the reading corner program contributes to fostering students' interest in reading children's literature and should be continuously optimized through sustainable management and the provision of more diverse book collections.